Evaluation of the patchouli essential oil (Pogostemon cablin Benth.) aromatic characteristic by near‐infrared spectroscopy - Diego Mauricio Cano-Reinoso; Yohanes Aris Purwanto; I Wayan Budiastra; Shinichiro Kuroki; Sutrisno Sutrisno; Slamet Widodo (Universitas Gadjah Mada, 2023)
This study aimed to evaluate the aromatic characteristic of patchouli essential oil (Pogostemon cablin Benth.) by near‐infrared spectroscopy combined with chemometric treatments. The study used 84 oil samples collected from around Indonesia, namely in Konawe, Kolaka, Bogor, Garut, Aceh, Jambi, and Masamba. Several pretreatments were used to process the spectral data, together with the application of partial least squares. The spectrum wavelength applied was between 1000 and 2500 nm. The spectra data were separated to develop two models based on their physical and chemical properties (Bogor, Garut, Konawe, and Kolaka in the first model; Aceh, Jambi, and Masamba in the second one). Liquid chromatography‐mass spectrometry (LC‐MS) was used as a reference method. Patchouli alcohol was established as the main chemical compound of this aromatic oil. The best calibration for the first model was that with mean center normalization as a data pretreatment, while for the second model, it was the one using the second derivative. Both models had a correlation coefficient higher than 0.90 and a coefficient of variation lower than 2.98%. In conclusion, near‐infrared spectroscopy can be employed as an accurate tool to determine the characteristic of patchouli oil.